An Analysis of Speech Functions in Spider-Man: No Way Home’s “I Lost Gwen” Scene - Anggraini, Putri Redni; Zega, Rio Ferdinand; Rangkuti, Linda Astuti; Sihite, Meida Rabia (EXCELLENCE: Journal of English and English Education, 2025)
This study analyzes the speech functions in the "I Lost Gwen" scene from the film Spider-Man: No Way Home using Halliday’s interpersonal metafunction. It focuses on how statements, questions, offers, and commands convey emotional pain, compassion, and mutual understanding. A qualitative descriptive method was applied to 14 clauses from a 91:36-minute film segment known for its emotional impact and virality. The findings show a dominance of congruent speech functions realized through declarative moods, reflecting Peter Parker’s expression of loss and vulnerability. Metaphorical realizations in clauses 7, 8, and 14 reveal indirect meanings, such as self-directed commands and disguised warnings, highlighting internal conflict and emotional nuance. The study demonstrates that speech functions choices reflect deeper interpersonal meanings and contribute to emotional depth in cinematic dialogue.